EVOLVING CONCEPTS RELATED TO ACHIEVING BENEFIT SHARING FOR CUSTODIANS OF TRADITIONAL KNOWLEDGE - Elvin-Lewis, Memory (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
In the context of evolving intellectual property law, defining ownership of traditional knowledge can be challenging when claims of origin are conflicting and requires accepting parameters of how uniqueness is defined and patent law is applied to protect this information. For purposes of this paper, the complexities of evolving benefit sharing for custodians of traditional knowledge are discussed in relationship to the use of medicinal plants. Parameters of ownership can vary not only by the perception of individuals that lay claim to the information but also by international, regional and national laws that govern how benefits should be fairly appropriated. Examples are provided to exemplify the wide variation that presently exists in this evolving process with illustrations of how this information, novel or otherwise, can be utilized to optimize its commercial worth.